Social work on trial : the Colwell Inquiry and the state of welfare - Butler, Ian, 1955- (Policy Press, 2011)
The public inquiry that followed the death of Maria Colwell had profound implications for the developing profession and practice of social work in the UK. This book describes both the local and national politics, professional concerns and public interest that surrounded the inquiry and its aftermath.